Maximal accumulated oxygen deficit (maod) of physically active females during mid-follicular and mid-luteal phases of ovarian cycle - Shazlin, Shaharudin (2008)
This intervention study was undertaken with an objective to evaluate the anaerobic capacity in repeated sprint cycling bouts during different phases of ovarian cycle. Twelve physically active females aged 22.41 ± 1.68 years, weight 52.06 ± 7.28 kg, height 158.17 ± 4.17 em, and V02maxof34.92 ± 4.85 ml·kg-1·min-1 contributed in this study. The method of measuring maximal accumulated oxygen deficit (MAOD) was implemented from Medb~ ·:·. al., (1988). Initially, the V02max of the participant were measured on cycle ergometer following a graded exercise protocol. Then, the participants did sub-maximal cycling exercise for 10 minutes at 50%, 60%, 70% and 80% of V02max on separate days. The linear regression determined from the V02-power relationship was used to approximate supramaximal power output at 120% V02max· Next, the participants performed repeated sprint cycling at 120% ofV02max intensity with .. ·: minutes rest between consecutive sprints during mid-follicular (MF) and mid-luteal (ML) phases. The menstrual phases were verified through daily basal body measurement and serum progesterone analysis. Results indicated there were no significant difference in maximal accumulated oxygen deficit (MAOD) and sprint performance between mid-follicular (MF) and mid-luteal (ML) phases in repeated sprint cycling. There was also no significant difference in plasma lactate and plasma ammonia concentration between mid-follicular (MF) and mid-luteal (ML) phases in repeated sprint cycling. Hence, it is concluded that the ovarian phases of women with regular menstrual cycle, have no significant effect on anaerobic capacity.